Flower Bud Differentiation in Pepper (Piper Nigrum L.) - Nalini P V (Department of Horticulture (Plantation Crops and Spices), College of Horticulture, 1983)
Studies were undertaken at the College of Horticulture, Vellanikkara during 1981-82 to collect information on the factors influencing flowering/flower bud differentiation in pepper and on the chronological development of the vegetative and floral buds. Carbon-nitrogen ratio exhibited a favourable influence on the differentiation of flower buds in pepper. Results of the path coefficient analysis and the data on the weather parameters considered together indicated rainfall as the most important factor influencing flower bud differentiation. Receipt of the pre-monsoon showers after a long spell of dry weather seemed to trigger the flower bud differentiation activity in pepper. Microtechniques for histological examination of pepper stem sections were standardised. Killing and fixing the specimens in FAA, dehydration in TBA serious and staining with saffranin gave satisfactory results. Differentiation of vegetative buds alone was observed in the two types of laterals (which bore the crop during the previous season and which did not). Three stages have been identified in the development of vegetative buds. Flower bud differentiation was observed in the shoots arising from the two types of laterals. Maximum flower bud differentiation occurred during June – July. Five stages were identified in the development of flower buds. The process of flower bud differentiation was seen completed within about 20 days of commencement.